Tricuspid Valve Replacement in Rheumatic Heart Disease - Braimbridge, M. V. (1970)
The diagnosis of tricuspid valve disease is often difficult; the best treatment is not yet established. Twenty patients had tricuspid valve replacements at St. Thomas's Hospital as part of multiple valve replacement procedures. The hospital mortality was 25%, most deaths being due to a low cardiac output causing hepatorenal failure. Preoperative cardiac cachexia had a fatal outcome in all cases. Except in two instances, surviving patients returned to a satisfactory level of activity.